Nurses’ perceptions of the ISBAR handover protocol and its relationship to the quality of handover: A case study of bilingual nurses - Pun, Jack (Frontiers in Psychology, 2023)
Introduction Poor communication at handover may cause harm to the patient. Despite numerous studies promoting ISBAR as a communication tool for structured handover, nurses have varied levels of understanding of the ISBAR tool; this may lead to different perceptions. This paper aims to explore the structural relationships between factors relating to handover communication among nurses. Method A path analysis was conducted to analyse how 206 bilingual nurses’ knowledge of the ISBAR affects the perceived quality of handover, using a validated Nursing Handover Perception Questionnaire. Results Nurses’ knowledge of the ISBAR was not a statistically significant factor affecting the perceived quality of handover. Rather, nurses’ understanding of patients’ care plans and receiving updated information about patients determine the perceived quality of handover. Discussion Nurses’ compliance with the ISBAR tool should be considered in order to further identify and develop effective communication skills. Nurses’ understanding of patients’ care plans and receiving updated patient information significantly corresponded to the perceived quality of handover.